Respuesta :
Answer:
an = -4 * (-3)^ (n-1)
513560652
Step-by-step explanation:
We can find the common ratio
12/-4 = -3
r =-3
The explicit formula is
an =a1 r^(n-1)
an = -4 * (-3)^ (n-1)
We want the 18 th term
a 18 = -4 (-3) ^ 17
513560652
Answer:
Nth term = (4/3) × (-3)^n
18th term: 516560652 or 4 × 3¹⁷
Step-by-step explanation:
-4, 12 , -36...
Are terms of a Geometric progression with:
First term = -4
Common ratio = 12/-4 = -3
Nth term = -4 × (-3)^(n-1)
= -4 × (-3)^(n)/(-3)
= (-4/-3) ×3^n
= (4/3) × (-3)^n
18th term: n = 18
-4 × (-3)^(18-1)
-4 × (-3)¹⁷
4 × 3¹⁷
516560652